On reductionism in communication studies - Boruszewski, Jarosław (Lingua Posnaniensis, 2017)
In contemporary philosophy of communication we have two competing views on communication. In short they are called message-centred and meaning-centred. The first one is described as reductionist because it reduces communication to transmission of information. In the article a distinction has been made between a purely transmissional approach, which does not have a reductionist character and the reductionist account, which in an unjustified manner, conflates the transmission problem with semantic issues. For this purpose, the concept of levels of analysis and considerations concerning a conduit metaphor were used. Given the limited application of the reductionist approach in communication studies, in the last section of the article an integration approach is proposed. Such an approach, while avoiding conflation of levels, allows for their combining and finding connections between them.